Pengembangan Model Bimbingan Belajar Quantum Learning Untuk Meningkatkan Kemandirian Belajar - Abdullatif, Ariqah (Universitas Negeri Makassar, 2018)
bstract: This research is research of Development of Quantum Learning Guidance Model, to remind Student Independence Student in SMAN 3 Polewali aimed at: (1) To know the description of the students' needs on the development of Quantum Learning guidance model in SMA Negeri 3 Polewali. (2) To know the description of feasibility test and acceptance of learning guidance model of Quantum Learning in SMA Negeri 3 polewali (3) To know the description of Quantum Learning guidance model developed by the researcher. While the method used is the procedure research and development (research and development). Which is based on research stages by Borg and Gall. Data analysis uses qualitative and quantitative data analysis. The results showed that: (1) Development of guidance model Learning quantum learning to improve self-reliance Learning Students get high scoring scale from experts and the response Very good from teachers counseling guidance and students that is acceptable and feasible For use in SMA Negeri 3 Polewali (2) Product development in the form of model of learning guidance of quantum learning to improve student's learning independence has made it easier for teachers to implement the program because it has been arranged systematically.Â